2019
DOI: 10.1177/0963689719880543
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of Human Wharton’s Jelly Mesenchymal Stem Cells Accelerates Mouse Sciatic Nerve Recovery and is Associated with Upregulated Neurotrophic Factor Expression

Abstract: Peripheral nerve regeneration following injury is often slow and impaired, which results in weakened and denervated muscle with subsequent atrophy. Human Wharton’s jelly mesenchymal stem cells (hWJ-MSC) have potential regenerative properties which, however, remain unknown in mouse nerve recovery. This study investigated the effect of the topical application of hWJ-MSC onto repairing transected sciatic nerves in a mouse model. Human adipocyte-derived stem cells (hADSC) were used as a positive control. The sciat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Our previous study demonstrated that the topical application of hWJ-MSC accelerates signs of sciatic nerve recovery, such as five-toe spread and toe-off phase, partly via the direct upregulation and release of neurotrophic factors ( Supplementary Figure S1A,B ) [ 10 ]. To investigate the immunomodulatory effects of hWJ-MSC on sciatic nerve recovery, various immune cell populations were analyzed after hWJ-MSC administration to the nerve coaptation site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study demonstrated that the topical application of hWJ-MSC accelerates signs of sciatic nerve recovery, such as five-toe spread and toe-off phase, partly via the direct upregulation and release of neurotrophic factors ( Supplementary Figure S1A,B ) [ 10 ]. To investigate the immunomodulatory effects of hWJ-MSC on sciatic nerve recovery, various immune cell populations were analyzed after hWJ-MSC administration to the nerve coaptation site.…”
Section: Resultsmentioning
confidence: 99%
“…MSC can be isolated from Wharton’s jelly from the umbilical cord, which contains mucoid connective tissue and fibroblast-like cells. Our previous study demonstrated that the topical application of human Wharton’s jelly-derived MSC (hWJ-MSC) promote sciatic nerve recovery and regeneration because of the direct upregulation and release of neurotrophic factors [ 10 ]. MSC also exhibit diverse immunomodulatory effects, in addition to their regenerative property [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Five-toe spread analysis represents the intrinsic muscle recovery and indicates the signal transmission recovery after nerve transection [ 9 , 11 , 12 ]. In the present study, the distance of the five-toe spread was estimated in each mouse before the nerve transection.…”
Section: Methodsmentioning
confidence: 99%
“…Nerve injuries far from end-target organs, such as muscles, need a much longer time to regenerate, resulting in the atrophy of motor end-plates and muscles [ 7 ]. New strategies are being developed in a great deal of research for the improvement of peripheral nerve regeneration, which ameliorates the outcomes following nerve injury [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Schwann cell (SC), is the main glial cell in PNS, and it is pivotal in regulating the regeneration of peripheral nerves [ 4 , 5 ]. Reportedly, SCs can produce and secrete nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF), which are implicated in the post-PNI growth and regeneration processes of peripheral nerve [ 6 10 ]. Promoting the multiplication and migration of SCs can improve the regeneration of peripheral nerves [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%